Bad to good : achieving high quality and impact in your research - Woodside, Arch G. (Emerald Group Publishing Limited, 2016)
For decades, scholars have bemoaned the low relevancy and impact of most research in the leading journals in business, management, and marketing. The majority of the research that gets published, perhaps 70% of it, hardly has any measurable scholarly impact in terms of citations. Rather than low relevancy, "Bad to Good" posits that the deeper issue is the pervasive use of bad research practices appearing in most articles in almost all ranked journals in the sub-disciplines of business.With the objective of reducing the high volume of bad practices in research in finance, management and marketing, the book offers tools for improving theory construction and empirical testing of theory especially by early-to-mid scholars. "Bad to Good" covers 24 common bad practices, explaining why they are bad and how to replace them with good practices.Arch Woodside is a leading voice on how to improve business research. He served as the Editor-in-Chief of the "Journal of Business Research" (JBR) for forty years. In 2016 the JBR ranked first among the top-twenty journals in marketing in the Google.com/scholar h-5 index (an impact metric) and seventh among the strategic management sub-discipline.
Includes bibliographical references and index.
Print version record
Keywords: Research -- Methodology; Education -- Research; Research methods: general